The Degree of Practicing Innovative Leadership by Administrative Leaders at the Educational General Directorates in the Sultanate of Oman - Mohammed S. Al-Jaraiyda; Berdriya K. AL-Jahwari (Sultan Qaboos University, 2014)
This study aims at identifying the degree of practicing innovative leadership by the administrative leaders at the General directorates of the Ministry of Education in the Sultanate of Oman. To achieve the objective of the study, a questionnaire composed of 41 items was designed. After checking the validity and reliability of the questionnaire, 165 leaders, general managers and their deputies, district managers and their deputies and heads of divisions were asked to respond to the questionnaire during the academic year 2011-2012. To evaluate the responses, several statistical procedures were used: means, standard deviations, ANOVA and Ttest. The study found that the degree of practicing innovative administrative leadership among the administrative leaders of the general directorates in the Sultanate of Oman was high. The results also indicated the presence of statistically significant differences (p < 0.05) due to gender and in favor of females. There was no significant differences (p = 0.05) due to academic qualifications and years of experience. In the light of the findings, the researchers recommend the implementation of the principle of participation in decision-making among the employees of the general directorates of the Ministry of Education.